2011
DOI: 10.1093/hmg/ddr303
|View full text |Cite
|
Sign up to set email alerts
|

European genome-wide association study identifies SLC14A1 as a new urinary bladder cancer susceptibility gene

Abstract: Three genome-wide association studies in Europe and the USA have reported eight urinary bladder cancer (UBC) susceptibility loci. Using extended case and control series and 1000 Genomes imputations of 5 340 737 single-nucleotide polymorphisms (SNPs), we searched for additional loci in the European GWAS. The discovery sample set consisted of 1631 cases and 3822 controls from the Netherlands and 603 cases and 37 781 controls from Iceland. For follow-up, we used 3790 cases and 7507 controls from 13 sample sets of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
90
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(94 citation statements)
references
References 52 publications
1
90
0
3
Order By: Relevance
“…3 Then additional predisposing loci, 5p15.33 (rs2736098 and rs401681), 4p16.3 (rs798766), 22q13.1 (rs1014971), 19q12 (rs8102137), 2q37.1 (rs11892031), 18q12.3 (rs17674580, rs7238033, rs10775480 and rs10853535), 3q26.2 (rs10936599) and 11p15.5 (rs907611), were identified by other GWAS in Caucasian, respectively. [4][5][6][7][8][9] Further, large candidate gene and metaanalysis studies revealed NAT2 slow acetylation and GSTM1 null genotypes as susceptibility loci for bladder cancer. 10,11 Although the aforementioned loci associated with bladder cancer risk have been successfully performed in the populations of European ancestry, the individual effect of these risk variants in other populations is as yet unknown.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…3 Then additional predisposing loci, 5p15.33 (rs2736098 and rs401681), 4p16.3 (rs798766), 22q13.1 (rs1014971), 19q12 (rs8102137), 2q37.1 (rs11892031), 18q12.3 (rs17674580, rs7238033, rs10775480 and rs10853535), 3q26.2 (rs10936599) and 11p15.5 (rs907611), were identified by other GWAS in Caucasian, respectively. [4][5][6][7][8][9] Further, large candidate gene and metaanalysis studies revealed NAT2 slow acetylation and GSTM1 null genotypes as susceptibility loci for bladder cancer. 10,11 Although the aforementioned loci associated with bladder cancer risk have been successfully performed in the populations of European ancestry, the individual effect of these risk variants in other populations is as yet unknown.…”
mentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9] The SNPs rs9642880 at 8q24.21 and rs710521 at 3q28 were the first to be identified as common susceptibility loci for bladder cancer in nine study groups of European ancestry.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, genomewide association studies (GWAS) have permitted the identification of novel susceptibility loci in the human genome associated with many complex diseases, including cancer (Dudek et al, 2013). To date, three GWAS for bladder cancer risk have been conducted, and eight single nucleotide polymorphisms (SNPs) were identified near the following genes: MYC (8q24), TP63 (3q28), PSCA (8q24), FGFR3/TACC3 (4p16), CBX6/ APOBEC3A (22q13), CCNE1 (19q12), UGT1A (2q37), and SLC14A1 (18q12) (Kiemeney et al, 2008;Wu et al, 2009;Kiemeney et al, 2010;Rothman et al, 2010;Rafnar et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, large efforts have been invested into genome-wide association studies to identify genetic variants that confer urinary bladder cancer risk (Rothman et al 2010;Selinski 2014C;Rafnar et al 2014Rafnar et al , 2011Rafnar et al , 2009Kiemeney et al 2008Kiemeney et al , 2010Garcia-Closas et al 2011;Figueroa et al 2016Figueroa et al , 2014. Usually, the odds ratios of individual variants are low and do not exceed 1.4 (Selinski 2012(Selinski , 2014aGolka et al 2011;Schwender et al 2012).…”
mentioning
confidence: 99%